2022
DOI: 10.3390/cancers14112586
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Monitoring Technology for Pediatric Thyroidectomy

Abstract: This retrospective study aimed to describe, firstly, characteristics and outcomes of the intraoperative neural monitoring technology in the pediatric population, and secondarily the recurrent laryngeal nerve complication rate. Thirty-seven patients (age <18 years) operated on from 2015 to 2021 by conventional open thyroid surgery were included. Twenty-four (64.9%) total thyroidectomies and 13 (35.1%) lobectomies were performed. Seven central and six lateral lymph node dissections completed 13 bilateral proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Prior researches, especially in adults, showed that IONM combined with visual RLN identification considerably reduces postoperative RLN palsy rates [ 4 , 8 , 9 , 19 , 20 , 21 , 22 ], without lengthening the surgical procedure [ 23 , 24 ]. Especially in complicated operations, such as re-operations, residual thyroidectomy, or inflammation, the RLN may be encased within or displaced by scar tissue, making its visual identification challenging and time-consuming, even for experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Prior researches, especially in adults, showed that IONM combined with visual RLN identification considerably reduces postoperative RLN palsy rates [ 4 , 8 , 9 , 19 , 20 , 21 , 22 ], without lengthening the surgical procedure [ 23 , 24 ]. Especially in complicated operations, such as re-operations, residual thyroidectomy, or inflammation, the RLN may be encased within or displaced by scar tissue, making its visual identification challenging and time-consuming, even for experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%